Crop load, fruit russeting, vegetative growth traits and leaf nutrient effects as a function of customized foliar nutritive fluids in Gale Gala apple (Malus × domestica) in dry temperate environment - PRAMOD KUMAR; RAJESHWAR S CHANDEL; ANIL KUMAR; NAVEEN C SHARMA (The Indian Journal of Agricultural Sciences, 2023)
The study exploited the clonal rootstocks for bio-efficacy testing of water soluble customized nutrient (WSCN), viz. K2O:S:Mg:Ca:Zn:B (6:11:5:0.3:0.3:0.4, w/w) on agronomic performance, fruit yield and quality characteristics on Gale Gala apple (Malus × domestica Borkh.) grafted onto EMLA.111 and EMLA.7 clonal rootstocks in dry temperate climatic conditions of north-west Himalaya. The trial procedure included tree fertilization of four levels of NPK soil fertilizers (100, 80, 60 and 40% of recommended dose of fertilizers (RDF-NPK, 70:35:70, one-year-old tree basis) were supplemented along with WSCN foliar formulation. Application of 60% RDF+75g WSCN+25g urea at 15 DAPF followed by 75g WSCN at 30 and 45 DAPF improved growth traits, fruit coloration, fruit yield and quality attributes. All applied concentrations of WSCN reduced russeting in Gale Gala apple significantly. The effects of the integrated fertilizers schedules with WSCN on russet control were also evaluated. EMLA.111 was the most suitable clonal rootstock, where, the rate of russeting on fruits was less compared to EMLA.7 irrespective of the WSCN treatments tested. The phenological observations in relation to the initiation of the flowering lasting for 19 days were also recorded. The pest management programme was adopted to manage the apple pest complex. Between the different schedules with foliar WSCN, the differences were also recorded in amount of russeting on EMLA.111/ EMLA.7 rootstocks compared to control. The schedules with foliar WSCN on a wet canopy noticed less russetted fruits. The study also identified the relationship between yield and productivity traits using path coefficient analysis to know the direct and indirect effects of independent variables on managerial ability of the crop. Principle component analysis (PCA) of fruit quality traits was also worked out for differences among WSCN formulations tested which accounted 100% of the cumulative variance.